»Spiritualität« im Christentum und darüber hinaus: Soziologische Vermutungen zur Hochkonjunktur eines Begriffs - Ebertz, Michael N. (Zeitschrift für Religionswissenschaft, 2005)
It is obvious to the society in general as among Christians in particular the meaning of transcendences has lost its traditional foundation and has been pluralised. The expression »religion« has been substituted for by »spirituality« and »piety«. To a diminishing degree »religion« stands for a specifically Christian creed, even less so for the creed in the personal Christian god as the source of the secrets of life. A definition of those aspects of spirituality is proposed that are contained in the communicative budget of contemporary society. The paper will delineate the societal contexts of this definition and sketch the differentiated social forms connected to this notion by means a typology.